The association between ultra-processed food exposure and cognition in older adults - Sarah Gauci; Belayneh Mengist; Mojtaba Lotfaliany; Malcolm Forbes; Farzaneh Asoudeh; Deb Junyi Zhang; Suzanne G. Orchard; Alice J. Owen; Daniel Clayton-Chubb; Robyn L. Woods; John J. McNeil; Joanne Ryan; et al. (GeroScience, 2026)
With an ageing population comes a growing burden of age-related cognitive decline. While evidence supports a relationship between higher diet quality and better cognitive outcomes, the association between ultra-processed foods (UPFs) and cognitive function remains underexplored. We examined this association using prospective data from the ASPirin in Reducing Events in the Elderly (ASPREE) study, a cohort of Australian adults aged 70 years and older. Dietary intake was assessed via a mail-based diet screening questionnaire and categorised according to the Nova classification. Cognitive performance was assessed using the Controlled Oral Word Association Test (COWAT), Symbol Digit Modalities Test (SDMT), Hopkins Verbal Learning Test–Revised (HVLT-R), Modified Mini-Mental State Examination (3MS), and a composite cognitive Z score. Participants were stratified into high UPF (≥ 4 servings/day) and low UPF (< 4 servings/day). Marginal structural models with inverse probability of treatment weighting estimated associations, adjusting for demographic, lifestyle, and clinical confounders. Among 11,502 participants (3505 high UPF; 7997 low UPF), over a median follow-up of 5.6 (± 2.4) years, higher UPF consumption was associated with poorer performance on the 3MS (mean difference –0.28, 95% CI –0.52 to –0.04), COWAT (–0.23, 95% CI –0.44 to –0.03), SDMT (–0.51, 95% CI –0.94 to –0.08), and the composite Z score (–0.04, 95% CI –0.07 to –0.01), but not HVLT-R (–0.12, 95% CI –0.26 to 0.02). Higher UPF intake was associated with poorer cognitive performance across multiple domains. These findings support initiatives to reduce UPF exposure as a potential strategy to promote healthy cognitive ageing.

Geomorphological and ecological change in a coastal foreland dune system, Sandscale haws, Cumbria, UK: the management challenges posed by climate change - Kenneth Pye; Simon J. Blott; Neil Forbes; Lindsay C. Maskell (Journal of Coastal Conservation, 2020)